Analysis of Complete Nucleotide Sequences of Angolan Hepatitis B Virus Isolates Reveals the Existence of a Separate Lineage within Genotype E - Lago, Barbara V.; Mello, Francisco C.; Ribas, Flavia S.; Valente, Fatima; Soares, Caroline C.; Niel, Christian; Gomes, Selma A. (PloS one, 2014)
Hepatitis B virus genotype E (HBV/E) is highly prevalent in Western Africa. In this work, 30 HBV/E isolates from HBsAg positive Angolans (staff and visitors of a private hospital in Luanda) were genetically characterized: 16 of them were completely sequenced and the pre-S/S sequences of the remaining 14 were determined. A high proportion (12/30, 40%) of subjects tested positive for both HBsAg and anti-HBs markers. Deduced amino acid sequences revealed the existence of specific substitutions and deletions in the B- and T-cell epitopes of the surface antigen (pre-S1- and pre-S2 regions) of the virus isolates derived from 8/12 individuals with concurrent HBsAg/anti-HBs. Phylogenetic analysis performed with 231 HBV/E full-length sequences, including 16 from this study, showed that all isolates from Angola, Namibia and the Democratic Republic of Congo (n = 28) clustered in a separate lineage, divergent from the HBV/E isolates from nine other African countries, namely Cameroon, Central African Republic, Côte d'Ivoire, Ghana, Guinea, Madagascar, Niger, Nigeria and Sudan, with a Bayesian posterior probability of 1. Five specific mutations, namely small S protein T57I, polymerase Q177H, G245W and M612L, and X protein V30L, were observed in 79-96% of the isolates of the separate lineage, compared to a frequency of 0-12% among the other HBV/E African isolates.